2017
DOI: 10.1042/bsr20170053
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic regulation of the circadian clock: role of 5-aza-2′-deoxycytidine

Abstract: We have been investigating transcriptional regulation of the BMAL1 gene, a critical component of the mammalian clock system including DNA methylation. Here, a more detailed analysis of the regulation of DNA methylation of BMAL1 proceeded in RPMI8402 lymphoma cells. We found that CpG islands in the BMAL1 and the PER2 promoters were hyper- and hypomethylated, respectively and that 5-aza-2′-deoxycytidine (aza-dC) not only enhanced PER2 gene expression but also PER2 oscillation within 24 h in RPMI8402 cells. That … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 48 publications
1
9
0
1
Order By: Relevance
“…Taniguchi et al reported that CpG islands of the Bmal1 promoter are hypermethylated in diffuse large B-cell lymphoma and in acute lymphocytic and myeloid leukaemia [42]. We also reported this phenomenon and that the methylation pattern of the Per2 promoter region does not change in RPMI8402 cells [46]. The aberrant methylation pattern of the Bmal1 promoter was restored, and the intrinsic rhythm was revived after 1 day of aza-dC treatment.…”
Section: Cancersupporting
confidence: 71%
See 1 more Smart Citation
“…Taniguchi et al reported that CpG islands of the Bmal1 promoter are hypermethylated in diffuse large B-cell lymphoma and in acute lymphocytic and myeloid leukaemia [42]. We also reported this phenomenon and that the methylation pattern of the Per2 promoter region does not change in RPMI8402 cells [46]. The aberrant methylation pattern of the Bmal1 promoter was restored, and the intrinsic rhythm was revived after 1 day of aza-dC treatment.…”
Section: Cancersupporting
confidence: 71%
“…We recently found that recovery from DNA methylation by 5-aza-2 0 -deoxycytidine (aza-dC) differs between the Bmal1 and Rpib9 genes, suggesting that the release of methylation depends on the locus/gene or sequence and that methylation status is specific to the DNA site [46]. Taken together, these findings imply that methylation is specific to gene function and that an early response to the aza-dC demethylation of sites in Bmal1 might be functionally important for adaptation to environmental change.…”
Section: Transcriptional Regulation Of the Bmal1 Genementioning
confidence: 99%
“…In specific cases, this remains, of course, a possibility for downregulation. However, in some detailed investigations, the Per2 promoter was instead found to be hypomethylated, despite the observed suppression of the gene [46,47]. This is, however, also explainable under conditions of silenced Bmal1, because the BMAL1 protein is required for Per2 expression.…”
Section: Circadian Oscillators and Melatonin In The Context Of Dna Momentioning
confidence: 98%
“…In several ovarian cancer cell lines, methylation at Bmal1 was associated with silencing of this gene, although this was accompanied by enhanced histone methylation (H3K27me3) [44]. In various other tumor cell lines, hypermethylation of the Bmal1 promoter was shown to silence this gene and to suppress circadian rhythmicity [11,25,[45][46][47]. Hypermethylation of a CpG island in the 5' region and hypomethylation in the first exon of Bmal1 were reported for cases of bipolar disorder [48].…”
Section: Circadian Oscillators and Melatonin In The Context Of Dna Momentioning
confidence: 99%
“…Joska et al argue that because perturbation of the circadian clock will alter the methylation status, hypermethylation of clock genes in cancer cells may simply be a result of defective clock gene expression and its impact on DNA methylation patterns . Interestingly, however, reversing DNA methylation, via treatment with a methylation inhibitor, such as 5‐aza‐2′‐deoxycytidine, regenerates endogenous circadian rhythms in RPMI8402 lymphoblastic leukaemia cells, via restoration of BMAL1 expression , suggesting that hypermethylation of circadian clock genes might be a mechanism by which circadian rhythms are suppressed within tumour cells.…”
Section: Core Circadian Clock Genes Are Dysregulated In Cancer Cellsmentioning
confidence: 99%